An exploration of working with grade 11 life sciences educators on the use of Virtual Lab to mediate learning of energy transformations - Shambare, Brian (Rhodes University, Faculty of Education, Department of Education)
The Department of Basic Education (DBE) examiners' diagnostic reports for 2012-2019 indicate that National Senior Certificate (NSC) learners mostly perform poorly in examination questions based on scientific investigations. The low performance by learners in these questions has been attributed to the failure by teachers to effectively mediate the learning of scientific concepts due to lack of science laboratories or poorly resourced laboratories in most rural schools. As a result, most learners are finding that scientific concepts are decontextualized and hence abstract. Thus, this study explored making use of Virtual Lab to mediate learning of scientific investigations using the topic Energy transformations. The study was located within an interpretive paradigm and a qualitative case study approach was employed. The study was conducted in four different rural schools in the Joe Gqabi district and seven Grade 11 Life Sciences teachers participated. Data was generated using semi-structured questionnaires, semi-structured interviews, lesson observation, workshop discussions, and journal reflections. The study was informed by Vygotsky's (1978) Socio-Cultural Theory (SCT) as the theoretical framework, and Thompson and Mishra's (2006) Technological Pedagogical Content Knowledge (TPACK) as the analytical framework. The results of this study showed that most educators have a positive predisposition towards the integration of Information and Communication Technologies (ICT) in their practice. The study found that using the Virtual Lab to teach Life Sciences has several benefits such as safe environment for conducting experiments; convenience and accessibility; positive teacher and learner attitudes and improvement on learner performance; elimination of physical limitations of a real lab; and availability top-class lab equipment and up-to-date reagents. The study also revealed some shortcomings that were associated with the use of the Virtual Lab. These are; lack of lab partner and peer-learning; and lack of direct supervision by a more knowledgeable facilitator. This study concluded that using the Virtual Lab enhances the quality of teaching scientific experiments in the selected under-resourced rural secondary schools. The study recommends the adoption of the Virtual Lab as a viable alternative to the conventional lab.
Keywords: Life sciences -- Study and teaching (Secondary) -- South Africa -- Eastern Cape; Energy conversion -- Study and teaching; Educational technology -- South Africa -- Eastern Cape; Teaching -- Aids and devices; Virtual Lab